A bench scale study on the startup, performance and optimization of the biological degradation of obnoxious air containing trimethylamine. Issue 1 (February 2020) - Raj, Ishan; Gupta, Ankit; Bansiwal, Amit; Vaidya, A.N.
Graphical abstract: Highlights: Biotrickling filter was examined in the steady and transient state conditions. Removal efficiency decreases with increase in the concentration. Main outcome of filter profile were statistically important with low P values. Similar distribution of the variables were evident from residual plots After long phase of starvation, the biotrickling filter was competent to recuperate. Abstract: Trimethylamine [TMA] possess various toxic and contributes a hazardous impact on the living organism. The best treatment to eradicate TMA has to be explored and checked. The operation of a biotrickling filter seeded with Agromyces and Ochrobactrum sp. was optimized for degrading trimethylamine [TMA]. The filter bed was adjusted for continuous treating of TMA up to 20 days. The profile of TMA inlet concentration [IC] and air flow rate on the elimination capacity [EC] and removal efficiency [RE] was examined. A variation of RE [24.71–88.45%] in TMA degradation the filter bed was observed on different inlet loading rates [ILR]. The highest RE and microbial growth was recorded at a height of 45 cm. The output values were statistically deduced by carrying out an analysis of variance [ANOVA] to explicate the key and interacting properties. The biotrickling filter stability was also successfully determined with a temporary shutdown for a prolonged period of 15 days. The maximum EC attained for TMA was 29.28 g m -3 h -1 at inlet loading rate [ILR] of 57.6 g m -3 h -1 .